Special protection of the Ukrainian lands as the main national wealth: theoretical and legal aspects - Kulinich, P.; Novakovska, I. (Land Management, Cadastre and Land Monitoring, 2022)
Abstract.  With a unique soil cover, Ukraine has been leading in the production and world export of grain crops and sunflower, providing grain needs for 400 million people in recent years. However, an unbalanced scarce farming system has caused increased soil degradation and a decrease in its fertility level. In connection with this, the relevance of the protection and rational use of land has increased significantly, as the tendency to worsen the quality of land has intensified, and sometimes it became a crisis. Russian aggression has led to the seizure and destruction of part of the land resource, soil cover pollution, mining of significant territories, direct physical damage to Ukrainian black soil.The article is aimed at studying the implementation in the country of the constitutional provision for the special protection of land as the main national wealth, as well as the main directions of ensuring the reproduction and increase of soil fertility. The relationship between land and civil law is analyzed, the peculiarities of the presentation of the provisions of Article 14 of the provisions of the Constitution of Ukraine, Civil Code, Law of Ukraine "On Land Protection"  are disclosed.The necessity of improving a number of provisions of the Law of Ukraine "On Land Protection", the legal regime of especially valuable lands is substantiated, preservation of independence of land law as a separate legal system.Keywords: special protection of land, constitutional status, land legislation, categories of land, national wealth, especially valuable land, land resource potential